High-strength retarded magnesium phosphate cement as well as preparation method and application thereof

By using composite retarders and a variety of additives in magnesium phosphate cement, the problem of difficult control of the settling time and insufficient mechanical properties of magnesium phosphate cement is solved, the controllability and mechanical properties of the settling time are achieved, and its application scenarios are expanded.

CN119859028AActive Publication Date: 2025-04-22DALIAN UNIV OF TECH

Patent Information

Application Number
CN202510066702.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The settling time of magnesium phosphate cement is difficult to control, resulting in poor construction operability and insufficient mechanical properties, which limits its application scenarios.

Method used

Compound retarders are used, including sodium tripolyphosphate, zinc acetate, disodium EDTA and polyacrylic acid, combined with recalcined magnesium oxide powder, phosphate, blends, fly ash microbeads, carbon nanotubes and carbon fibers, and the setting time of magnesium phosphate cement is controlled by regulating the dosage and component ratio of the composite retarder, and the settling time of magnesium phosphate cement is improved.

Benefits of technology

The controllable adjustment of the settling time of magnesium phosphate cement is achieved, and the settling time can be adjusted between dozens of minutes and tens of hours, which significantly improves its mechanical properties and construction operability and expands application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244466810000131
    Figure BDA0005244466810000131
  • Figure BDA0005244466810000141
    Figure BDA0005244466810000141
Patent Text Reader

Abstract

The invention provides high-strength retarded magnesium phosphate cement as well as a preparation method and application thereof, and belongs to the technical field of magnesium phosphate cement. The high-strength retarded magnesium phosphate cement provided by the invention is prepared from the following raw materials in parts by mass: 60 to 95 parts of dead burned magnesia powder, 20 to 50 parts of phosphate, 3 to 15 parts of a composite retarder, 5 to 20 parts of an admixture, 8 to 14 parts of fly ash microspheres, 1 to 2 parts of carbon nanotubes, 1 to 5 parts of carbon fibers and 5 to 30 parts of water, the composite retarder comprises sodium tripolyphosphate, zinc acetate, EDTA (Ethylene Diamine Tetraacetic Acid) disodium and polyacrylic acid; the admixture comprises phosphorus slag powder and silica fume. The result of the embodiment shows that the setting time of the high-strength delayed-setting magnesium phosphate cement provided by the invention is controllable between dozens of minutes and dozens of hours, meanwhile, the compressive strength of the magnesium phosphate cement 28d is greater than 90MPa, and the magnesium phosphate cement has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium phosphate cement, and in particular to high-strength slow-setting magnesium phosphate cement and a preparation method and application thereof. Background Art

[0002] Magnesium phosphate cement is a new type of phosphate repair material with early strength and fast hardening, usually composed of magnesium oxide, phosphate and retarder. Compared with ordinary Portland cement, magnesium phosphate cement has the advantages of fast low-temperature setting, high early strength, small shrinkage, good wear resistance and frost resistance, as well as good compatibility with the original concrete and good biocompatibility. Therefore, it is widely used in the fields of rapid repair of roads, bridges and airport runways, as well as the solidification of harmful and radioactive materials, and has important civil and military uses.

[0003] However, magnesium phosphate cement also has some significant defects, such as too fast coagulation, large hydration heat release, low overall strength and poor construction operability. In actual projects, due to the sensitivity of magnesium phosphate cement to temperature, if it is improperly operated, the cementitious material will coagulate during mixing, resulting in material failure and engineering accidents. The coagulation time has become an important factor restricting the application of magnesium phosphate cement, so it is necessary to modify the performance of magnesium phosphate cement. However, the gelling principle of magnesium phosphate cement and ordinary silicate cement is different from that of ordinary silicate cement, which generates hydrated calcium silicate and other components through hydration reaction. The reaction mechanism of magnesium phosphate cement is acid-base reaction, forming chemically bonded compounds to produce gelling effect, and its main strength providing components are compounds such as magnesium potassium phosphate, which makes many reinforcement methods that can be used in silicate cement become inapplicable in magnesium phosphate cement.

[0004] After extensive research on the basic components, modified materials and retarder development of magnesium phosphate cement, it was found that the type and dosage of retarder have the most significant impact on the setting time of magnesium phosphate cementitious materials. However, the current retarders can only delay the setting speed of magnesium phosphate cement to avoid serious strength loss, but cannot regulate the setting time of magnesium phosphate cement, which greatly limits the application scenarios of magnesium phosphate cement. At the same time, the mechanical properties of the prepared magnesium phosphate cement are average, making it difficult to further promote and apply.

[0005] Therefore, how to achieve controllable regulation of the setting time of magnesium phosphate cement and improve the mechanical properties of magnesium phosphate cement has become a technical problem to be solved urgently in this field. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength slow-setting magnesium phosphate cement and a preparation method and application thereof. The high-strength slow-setting magnesium phosphate cement provided by the present invention can realize controllable adjustment of the setting time, and the magnesium phosphate cement has excellent mechanical properties.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a high-strength slow-setting magnesium phosphate cement, which comprises the following raw materials, by weight: 60 to 95 parts of dead-burned magnesium oxide powder, 20 to 50 parts of phosphate, 3 to 15 parts of composite retarder, 5 to 20 parts of admixture, 8 to 14 parts of fly ash microbeads, 1 to 2 parts of carbon nanotubes, 1 to 5 parts of carbon fibers and 5 to 30 parts of water;

[0009] The composite retarder comprises sodium tripolyphosphate, zinc acetate, disodium EDTA and polyacrylic acid; and the admixture comprises phosphorus slag powder and silica fume.

[0010] Preferably, the average particle size of the dead-burned magnesium oxide powder is 30-40 μm, and the content of magnesium oxide in the dead-burned magnesium oxide powder is ≥92%.

[0011] Preferably, the phosphate includes one or two of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, aniline hypophosphite and isopropanolamine phosphate.

[0012] Preferably, the composite retarder comprises, by mass percentage, 27-43% sodium tripolyphosphate, 12-25% zinc acetate, 17-22% disodium EDTA and the balance polyacrylic acid.

[0013] Preferably, the composite retarder comprises, by mass percentage, 30-35% sodium tripolyphosphate, 15-20% zinc acetate, 18-21% disodium EDTA and the balance polyacrylic acid.

[0014] Preferably, the mass ratio of the phosphorus slag powder to silica fume is 1:(0.1-2).

[0015] Preferably, the average particle size of the fly ash microbeads is ≤0.5 μm, and the specific surface area of ​​the fly ash microbeads is ≥1000 m 2 / kg.

[0016] Preferably, the parameters of the carbon fiber include: a length of 2 to 10 mm, a diameter of 10 to 50 μm, a tensile strength of 1500 to 2400 MPa, and an elongation at break of 8 to 12%.

[0017] The present invention provides a method for preparing the high-strength slow-setting magnesium phosphate cement described in the above technical solution, comprising the following steps:

[0018] (1) mixing dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers to obtain a mixture;

[0019] (2) mixing the composite retarder and water, and then adding the mixture obtained in step (1) to stir, and finally curing to obtain high-strength retarded magnesium phosphate cement.

[0020] The present invention provides the use of the high-strength slow-setting magnesium phosphate cement described in the above technical solution or the high-strength slow-setting magnesium phosphate cement prepared by the preparation method described in the above technical solution in rapid repair and solidification of harmful and radioactive substances.

[0021] The present invention provides a high-strength slow-setting magnesium phosphate cement, which comprises the following raw materials by mass: 60-95 parts of dead-burned magnesium oxide powder, 20-50 parts of phosphate, 3-15 parts of composite retarder, 5-20 parts of admixture, 8-14 parts of fly ash microspheres, 1-2 parts of carbon nanotubes, 1-5 parts of carbon fiber and 5-30 parts of water; the composite retarder comprises sodium tripolyphosphate, zinc acetate, disodium EDTA and polyacrylic acid; the admixture comprises phosphorus slag powder and silica fume. In the present invention, dead-burned magnesium oxide powder can provide a large amount of magnesium oxide, and magnesium oxide can provide an acidic environment and acid radical ions through phosphate, and hydration reaction generates hydration products that improve the strength of magnesium phosphate cement, thereby obtaining high-performance magnesium phosphate cement; by using the composite retarder, the magnesium oxide in the magnesium phosphate cement paste can be combined with the Mg in the magnesium phosphate cement paste to form a hydration product that improves the strength of magnesium phosphate cement. 2+It has strong chelating ability, reduces the concentration of magnesium ions, and thus delays the formation of hydration products. Compared with an equal amount of a single type of retarder, the four components in the composite retarder can play a good synergistic role, further improving its retarding effect; by controlling the dosage of the composite retarder, the setting time of magnesium phosphate cement can be controlled to be controllable between tens of minutes and more than ten hours, so that it can be adjusted accordingly according to actual working conditions, greatly expanding the application scenarios of magnesium phosphate cement; by adding admixtures, on the one hand, the hydration reaction inside the magnesium phosphate cement can be inhibited in the early stage, thereby reducing the hydration rate, and on the other hand, the degree of hydration in the later stage can be increased, thereby improving the strength and water resistance of magnesium phosphate cement; fly ash The active ingredients in the microbeads can react chemically with the alkaline substances in magnesium phosphate cement, promote the hydration reaction of cement, improve the strength and durability of magnesium phosphate cement, and on the other hand, fill it in the gaps between magnesium phosphate cement particles, reduce the porosity of magnesium phosphate cement, and further improve the density and strength of magnesium phosphate cement; carbon nanotubes can significantly improve the internal structure of magnesium phosphate cement, improve its compactness, and then improve the mechanical properties and durability of magnesium phosphate cement; utilize the bridging polymerization effect of carbon fiber in cement-based materials to improve the tensile and flexural strength and deformation capacity of magnesium phosphate cement, and at the same time, the effect of consuming load energy can be achieved, thereby significantly enhancing the toughness and crack resistance of magnesium phosphate cement-based materials. The present invention can not only improve the early strength of phosphate cement by optimizing the composition and dosage of phosphate cement, but also significantly improve the slow setting effect, increase the setting time of phosphate cement, and improve the controllability of phosphate cement. The results of the examples show that the setting time of the high-strength slow-setting magnesium phosphate cement provided by the present invention can be controlled between tens of minutes and more than ten hours, and the compressive strength of the magnesium phosphate cement at 28 days is greater than 90 MPa, and it has excellent mechanical properties. DETAILED DESCRIPTION

[0022] The invention provides a high-strength slow-setting magnesium phosphate cement, which comprises the following raw materials, measured by weight: 60-95 parts of dead-burned magnesium oxide powder, 20-50 parts of phosphate, 3-15 parts of composite retarder, 5-20 parts of admixture, 8-14 parts of fly ash microbeads, 1-2 parts of carbon nanotubes, 1-5 parts of carbon fibers and 5-30 parts of water.

[0023] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 60 to 95 parts of dead-burned magnesium oxide powder by weight. In the present invention, the average particle size of the dead-burned magnesium oxide powder is preferably 30 to 40 μm; the content of magnesium oxide in the dead-burned magnesium oxide powder is preferably ≥ 92%. The present invention uses dead-burned magnesium oxide powder as the main raw material of magnesium phosphate cement, which is not only widely available, but also has a high magnesium oxide content, which can ensure that the prepared magnesium phosphate cement has good mechanical properties. As an embodiment of the present invention, the mass fraction of the dead-burned magnesium oxide powder can be 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or 90 parts; the average particle size of the dead-burned magnesium oxide powder can be 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm or 40 μm.

[0024] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 20 to 50 parts of phosphate based on 60 to 95 parts by mass of the dead-burned magnesium oxide powder. In the present invention, the phosphate preferably includes one or two of diammonium phosphate, dipotassium phosphate, aniline hypophosphite and isopropanolamine phosphate. The present invention can provide an acidic environment and acid radical ions for the hydration reaction by adding phosphate as a matrix component of the magnesium phosphate cement, thereby reacting with the dead-burned magnesium oxide powder to generate a hydration product that improves the strength of the magnesium phosphate cement, thereby obtaining high-performance magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the phosphate can be 25 parts, 30 parts, 35 parts, 40 parts or 45 parts.

[0025] Based on 60 to 95 parts by mass of dead-burned magnesium oxide powder, the high-strength slow-setting magnesium phosphate cement provided by the present invention includes 3 to 15 parts of composite retarder. In the present invention, the composite retarder includes sodium tripolyphosphate, zinc acetate, disodium EDTA and polyacrylic acid. In the present invention, the composite retarder preferably includes 27 to 43% sodium tripolyphosphate, 12 to 25% zinc acetate, 17 to 22% disodium EDTA and the balance polyacrylic acid, and more preferably 30 to 35% sodium tripolyphosphate, 15 to 20% zinc acetate, 18 to 21% disodium EDTA and the balance polyacrylic acid. The present invention uses the above-mentioned components as a composite retarder to react with Mg in magnesium phosphate cement paste. 2+It has a strong complexing ability, reduces the concentration of magnesium ions, and thus delays the generation of hydration products; at the same time, the above four components are used in combination, which can play a good synergistic role relative to the same amount of a single type of retarder, and further improve its retarding effect; by controlling the amount of the composite retarder, the setting time of magnesium phosphate cement can be controlled to be controllable between tens of minutes and more than ten hours, so that it can be adjusted accordingly according to the actual working conditions, greatly expanding the application scenarios of magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the composite retarder can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts.

[0026] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 5 to 20 parts of admixtures, based on 60 to 95 parts by mass of dead-burned magnesium oxide powder. In the present invention, the admixtures include phosphorus slag powder and silica fume; the mass ratio of the phosphorus slag powder to silica fume is preferably 1:(0.1 to 2). In the present invention, the content of P2O5 in the phosphorus slag powder is preferably ≥3wt%, and the content of soluble fluoride is preferably ≥2wt%; the specific surface area of ​​the phosphorus slag powder is preferably 300 to 600m 2 / kg; the average particle size of the silica fume is preferably 0.1-0.3μm. The present invention adopts phosphorus slag powder and silica fume as admixtures. The phosphorus slag powder can inhibit the hydration reaction inside the magnesium phosphate cement in the early stage, thereby reducing the hydration rate. At the same time, the phosphorus content is high and the specific surface area is large, which can react with magnesium oxide to reduce the content of free magnesium oxide in the cement in the later stage, improve the degree of hydration, and thus improve the strength and water resistance of magnesium phosphate cement; and silica fume can reduce the early hydration rate of magnesium phosphate cement and improve its early strength, which is beneficial to the normal construction and application of magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the admixture can be 8 parts, 10 parts, 12 parts, 15 parts or 18 parts; the specific surface area of ​​the phosphorus slag powder can be 400-500m 2 / kg; the average particle size of the silica fume can be 0.15-0.25 μm.

[0027] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 8 to 14 parts of fly ash microspheres, based on 60 to 95 parts by mass of the dead-burned magnesium oxide powder. In the present invention, the average particle size of the fly ash microspheres is preferably ≤0.5 μm; the specific surface area of ​​the fly ash microspheres is preferably ≥1000 m 2 / kg. The present invention adds fly ash microbeads to magnesium phosphate cement. On the one hand, the active ingredients in the fly ash can chemically react with the alkaline substances in the magnesium phosphate cement to promote the hydration reaction of the cement and improve the strength and durability of the magnesium phosphate cement. On the other hand, the addition in the form of fly ash microbeads can fill the gaps between the magnesium phosphate cement particles, reducing the porosity of the magnesium phosphate cement, thereby further improving the density and strength of the magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the fly ash microbeads can be 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or 90 parts; the average particle size of the fly ash microbeads can be 0.01 to 0.5 μm; the specific surface area of ​​the fly ash microbeads can be 1200 to 1500 m 2 / kg.

[0028] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 1 to 2 parts of carbon nanotubes based on 60 to 95 parts by mass of the dead-burned magnesium oxide powder. The present invention can significantly improve the internal structure of magnesium phosphate cement, improve its compactness, and thus improve the mechanical properties and durability of magnesium phosphate cement by adding a certain amount of carbon nanotubes to the magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the carbon nanotubes can be 1.2 parts, 1.4 parts, 1.6 parts or 1.8 parts.

[0029] According to the mass fraction of dead-burned magnesium oxide powder of 60 to 95 parts, the high-strength slow-setting magnesium phosphate cement provided by the present invention includes 1 to 5 parts of carbon fiber. In the present invention, the parameters of the carbon fiber preferably include: length of 2 to 10 mm, diameter of 10 to 50 μm, tensile strength of 1500 to 2400 MPa, and elongation at break of 8 to 12%. The present invention selects carbon fiber with excellent tensile strength and tensile properties as raw materials and adds them to magnesium phosphate cement, and utilizes the bridging polymerization effect of carbon fiber in cement-based materials to improve the tensile and flexural strength and deformation capacity of magnesium phosphate cement, and at the same time can achieve the effect of consuming load energy, thereby significantly enhancing the toughness and crack resistance of magnesium phosphate cement-based materials. As an embodiment of the present invention, the mass fraction of the carbon fiber can be 2, 3 or 4 parts; the parameters of the carbon fiber can be: length of 4 to 8 mm, diameter of 20 to 30 μm, tensile strength of 1800 to 2300 MPa, and elongation at break of 8 to 12%.

[0030] The high-strength slow-setting magnesium phosphate cement provided by the present invention includes 5 to 30 parts of water, based on 60 to 95 parts by mass of the dead-burned magnesium oxide powder. The present invention can control the amount of water, on the one hand, so that the slurry has good fluidity, and on the other hand, it can ensure the hydration reaction of the magnesium phosphate cement. As an embodiment of the present invention, the mass fraction of the water can be 10 parts, 15 parts, 20 parts or 25 parts.

[0031] The high-strength slow-setting magnesium phosphate cement provided by the present invention preferably further comprises 40 to 80 parts of aggregates, based on 60 to 95 parts by mass of the dead-burned magnesium oxide powder. In the present invention, the aggregate is preferably fine sand; the particle size of the aggregate is preferably 0.08 to 2.5 mm; the content of SiO2 in the fine sand is preferably ≥ 96%; and the mud content of the fine sand is preferably < 0.2%. By adding fine sand as aggregate, the strength of the high-strength slow-setting magnesium phosphate cement can be further improved.

[0032] In the present invention, unless otherwise specified, the above raw materials are all commercially available products well known to those skilled in the art or are prepared by preparation methods well known to those skilled in the art.

[0033] In the present invention, the dead-burned magnesium oxide powder can provide a large amount of magnesium oxide, and the magnesium oxide provides an acidic environment and acid radical ions through phosphate, and the hydration reaction generates a hydration product that improves the strength of magnesium phosphate cement, thereby obtaining high-performance magnesium phosphate cement; by using a composite retarder, the magnesium in the magnesium phosphate cement paste can be retarded. 2+ It has strong chelating ability, reduces the concentration of magnesium ions, and thus delays the formation of hydration products. Compared with an equal amount of a single type of retarder, the four components in the composite retarder can play a good synergistic role and further improve its retarding effect; by controlling the dosage of the composite retarder, the setting time of magnesium phosphate cement can be controlled to be controllable between tens of minutes and more than ten hours, so that it can be adjusted accordingly according to actual working conditions, greatly expanding the application scenarios of magnesium phosphate cement; by adding admixtures, on the one hand, the hydration reaction inside the magnesium phosphate cement can be inhibited in the early stage, thereby reducing the hydration rate, and on the other hand, the degree of hydration in the later stage can be increased, thereby improving the strength and water resistance of magnesium phosphate cement; fly ash The active ingredients in the microbeads can react chemically with the alkaline substances in magnesium phosphate cement, promote the hydration reaction of cement, improve the strength and durability of magnesium phosphate cement, and on the other hand, fill it in the gaps between magnesium phosphate cement particles, reduce the porosity of magnesium phosphate cement, and further improve the density and strength of magnesium phosphate cement; carbon nanotubes can significantly improve the internal structure of magnesium phosphate cement, improve its compactness, and then improve the mechanical properties and durability of magnesium phosphate cement; utilize the bridging polymerization effect of carbon fiber in cement-based materials to improve the tensile and flexural strength and deformation capacity of magnesium phosphate cement, and at the same time, the effect of consuming load energy can be achieved, thereby significantly enhancing the toughness and crack resistance of magnesium phosphate cement-based materials. The present invention can not only improve the early strength of phosphate cement by optimizing the composition and dosage of phosphate cement, but also significantly improve the slow setting effect, increase the setting time of phosphate cement, and improve the controllability of phosphate cement.

[0034] The present invention also provides a method for preparing the high-strength slow-setting magnesium phosphate cement described in the above technical solution, comprising the following steps:

[0035] (1) mixing dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers to obtain a mixture;

[0036] (2) mixing the composite retarder and water, and then adding the mixture obtained in step (1) to stir, and finally curing to obtain high-strength retarded magnesium phosphate cement.

[0037] The invention mixes dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers to obtain a mixture.

[0038] In the present invention, the mixing of the dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers is preferably carried out in a cement mortar mixer. The present invention has no particular limitation on the specific model and source of the cement mortar mixer, and a commercially available cement mortar mixer well known to those skilled in the art can be used. In an embodiment of the present invention, the cement mortar mixer is a JJ-15 cement mortar mixer.

[0039] In the present invention, the method of mixing the dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers is preferably as follows: firstly, the dead-burned magnesium oxide powder, phosphate, admixture and fly ash microbeads are mixed, and then the carbon nanotubes and carbon fibers are added in 2 to 5 times to obtain a mixture. In the present invention, the mixing is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring rate, which can be determined according to the technical common sense of those skilled in the art, so long as the components can be mixed evenly. In the present invention, the carbon nanotubes and carbon fibers are added in 2 to 5 times, which is conducive to their uniform dispersion in the mixture.

[0040] In the present invention, when the raw materials of the high-strength slow-setting magnesium phosphate cement further include aggregates, the aggregates are preferably mixed with dead-burned magnesium oxide powder, phosphate, admixtures and fly ash microspheres.

[0041] After obtaining the mixture, the present invention mixes the composite retarder with water, then adds the composite retarder into the mixture for stirring, and finally performs curing to obtain high-strength retarded magnesium phosphate cement.

[0042] In the present invention, the stirring time is preferably 40s to 240s. The present invention has no particular limitation on the stirring rate, which can be determined according to the technical common sense of those skilled in the art as long as the composite retarder and the components are uniformly mixed. As an embodiment of the present invention, the stirring time can be 60s, 80s, 100s, 120s, 140s, 160s, 180s, 200s or 220s.

[0043] After the stirring is completed, the present invention preferably pours the stirred slurry into a mold and then performs curing. The present invention has no particular limitation on the material and size of the mold, and a mold well known to those skilled in the art can be used. The present invention has no particular limitation on the specific operation of pouring the slurry into the mold, and an operation well known to those skilled in the art can be used.

[0044] The present invention does not specifically limit the specific method of curing, and curing can be performed using a curing method well known to those skilled in the art. In an embodiment of the present invention, the curing temperature may be room temperature; the curing method may be natural curing; during the natural curing process, the magnesium phosphate cement is kept moist by watering, so that the magnesium phosphate cement gradually hardens. The present invention preferably removes the mold after curing for 2 to 5 hours.

[0045] The preparation method provided by the invention is simple and can be prepared by using existing equipment. In addition, during the preparation process, the magnesium phosphate cement will not coagulate too quickly and release a large amount of heat during hydration, which will cause poor construction operability, thereby facilitating the large-scale promotion and use of phosphate cement.

[0046] The present invention also provides the use of the high-strength slow-setting magnesium phosphate cement described in the above technical solution or the high-strength slow-setting magnesium phosphate cement prepared by the preparation method described in the above technical solution in rapid repair and solidification of harmful and radioactive substances.

[0047] In the present invention, the rapid repair preferably includes rapid repair of roads, bridges and airports.

[0048] The present invention has no special limitation on the specific operation of the application, and conventional application operations well known to those skilled in the art may be used.

[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microspheres, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0052] The average particle size of the dead-burned magnesium oxide powder is 34.5 μm, and the content of magnesium oxide in the dead-burned magnesium oxide powder is 93.6%; the phosphate is potassium dihydrogen phosphate; the composite retarder is 37% sodium tripolyphosphate, 23% zinc acetate, 18% disodium EDTA and the balance polyacrylic acid in terms of mass percentage; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:2, the content of P2O5 in the phosphorus slag powder is 3.7wt%, the content of soluble fluoride is 2.1wt%, and the specific surface area of ​​the phosphorus slag powder is 543m 2 / kg; the average particle size of the silica fume is 0.24μm; the average particle size of the fly ash microspheres is 0.43μm, and the specific surface area of ​​the fly ash microspheres is 1246m 2 / kg; the length of the carbon fiber is 2 to 10 mm, the diameter is 10 to 50 μm, the tensile strength is 1500 to 2400 MPa, and the elongation at break is 8 to 12%;

[0053] The preparation method of the high-strength slow-setting magnesium phosphate cement is:

[0054] (1) First, add dead-burned magnesium oxide powder, phosphate, admixture and fly ash microbeads into a JJ-15 cement mortar mixer and stir for 60 seconds, then add carbon nanotubes and carbon fibers three times, each time with an interval of 30 seconds, and finally stir for 60 seconds to obtain a mixture;

[0055] (2) The composite retarder and water are mixed evenly, and then added to the mixture obtained in step (1) and stirred for 120 seconds, and then the stirred slurry is poured into a mold, and finally, the mold is demolded after curing in the air for 3 hours, and natural curing is continued to obtain high-strength slow-setting magnesium phosphate cement.

[0056] Example 2

[0057] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 75 parts of dead-burned magnesium oxide powder, 28 parts of phosphate, 12 parts of composite retarder, 14 parts of admixture, 10 parts of fly ash microspheres, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0058] The phosphate is ammonium dihydrogen phosphate; the composite retarder is 35% sodium tripolyphosphate, 25% zinc acetate, 17% disodium EDTA and the balance polyacrylic acid in terms of mass percentage; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:1.5;

[0059] Other conditions are the same as those in Example 1.

[0060] Example 3

[0061] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 68 parts of dead-burned magnesium oxide powder, 34 parts of phosphate, 9 parts of composite retarder, 16 parts of admixture, 9 parts of fly ash microspheres, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0062] In terms of mass percentage, the composite retarder is composed of 35% sodium tripolyphosphate, 25% zinc acetate, 17% disodium EDTA and the balance polyacrylic acid; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:1.5;

[0063] Other conditions are the same as those in Example 1.

[0064] Example 4

[0065] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 72 parts of dead-burned magnesium oxide powder, 30 parts of phosphate, 6 parts of composite retarder, 16 parts of admixture, 9 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0066] In terms of mass percentage, the composite retarder is composed of 41% sodium tripolyphosphate, 18% zinc acetate, 20% disodium EDTA and the balance polyacrylic acid; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:1.8;

[0067] Other conditions are the same as those in Example 1.

[0068] Example 5

[0069] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 65 parts of dead-burned magnesium oxide powder, 27 parts of phosphate, 3 parts of composite retarder, 11 parts of admixture, 12 parts of fly ash microspheres, 2 parts of carbon nanotubes, 3 parts of carbon fibers and 15 parts of water;

[0070] In terms of mass percentage, the composite retarder is composed of 41% sodium tripolyphosphate, 18% zinc acetate, 20% disodium EDTA and the balance polyacrylic acid; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:0.9;

[0071] Other conditions are the same as those in Example 1.

[0072] Example 6

[0073] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 65 parts of dead-burned magnesium oxide powder, 27 parts of phosphate, 3 parts of composite retarder, 8 parts of admixture, 12 parts of fly ash microspheres, 2 parts of carbon nanotubes, 3 parts of carbon fibers and 15 parts of water;

[0074] In terms of mass percentage, the composite retarder is composed of 41% sodium tripolyphosphate, 18% zinc acetate, 20% disodium EDTA and the balance polyacrylic acid; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:0.9;

[0075] Other conditions are the same as those in Example 1.

[0076] Example 7

[0077] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 72 parts of dead-burned magnesium oxide powder, 30 parts of phosphate, 6 parts of composite retarder, 5 parts of admixture, 9 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0078] Other conditions are the same as those in Example 4.

[0079] Example 8

[0080] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 72 parts of dead-burned magnesium oxide powder, 30 parts of phosphate, 6 parts of composite retarder, 8 parts of admixture, 9 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0081] Other conditions are the same as those in Example 4.

[0082] Example 9

[0083] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 72 parts of dead-burned magnesium oxide powder, 30 parts of phosphate, 6 parts of composite retarder, 12 parts of admixture, 9 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0084] Other conditions are the same as those in Example 4.

[0085] Example 10

[0086] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 72 parts of dead-burned magnesium oxide powder, 30 parts of phosphate, 6 parts of composite retarder, 20 parts of admixture, 9 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 15 parts of water;

[0087] Other conditions are the same as those in Example 4.

[0088] Embodiment 11

[0089] A high-strength slow-setting magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microspheres, 2 parts of carbon nanotubes, 2 parts of carbon fibers, 16 parts of water and 63 parts of aggregate;

[0090] The average particle size of the dead-burned magnesium oxide powder is 34.5 μm, and the content of magnesium oxide in the dead-burned magnesium oxide powder is 93.6%; the phosphate is potassium dihydrogen phosphate; the composite retarder is 37% sodium tripolyphosphate, 23% zinc acetate, 18% disodium EDTA and the balance polyacrylic acid in terms of mass percentage; the admixture is composed of phosphorus slag powder and silica fume in a mass ratio of 1:2, the content of P2O5 in the phosphorus slag powder is 3.7wt%, the content of soluble fluoride is 2.1wt%, and the specific surface area of ​​the phosphorus slag powder is 543m 2 / kg; the average particle size of the silica fume is 0.24μm; the average particle size of the fly ash microspheres is 0.43μm, and the specific surface area of ​​the fly ash microspheres is 1246m 2 / kg; the length of the carbon fiber is 2 to 10 mm, the diameter is 10 to 50 μm, the tensile strength is 1500 to 2400 MPa, and the elongation at break is 8 to 12%; the aggregate is fine sand with a particle size of 0.08 to 2.5 mm, the content of SiO2 in the fine sand is ≥96%, and the mud content of the fine sand is <0.2%;

[0091] The preparation method of the high-strength slow-setting magnesium phosphate cement is:

[0092] (1) First, add dead-burned magnesium oxide powder, phosphate, admixture, fly ash microspheres and aggregate into a JJ-15 cement mortar mixer and stir for 60 seconds, then add carbon nanotubes and carbon fibers three times, each time with an interval of 30 seconds, and finally stir for 60 seconds to obtain a mixture;

[0093] (2) The composite retarder and water are mixed evenly, and then added to the mixture obtained in step (1) and stirred for 120 seconds, and then the stirred slurry is poured into a mold, and finally, the mold is demolded after curing in the air for 3 hours, and natural curing is continued to obtain high-strength slow-setting magnesium phosphate cement.

[0094] Comparative Example 1

[0095] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0096] Other conditions are the same as those in Example 1.

[0097] Comparative Example 2

[0098] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 1 part of composite retarder, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0099] Other conditions are the same as those in Example 1.

[0100] Comparative Example 3

[0101] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 2 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0102] Other conditions are the same as those in Example 1.

[0103] Comparative Example 4

[0104] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0105] In terms of mass percentage, the composite retarder is 50% sodium tripolyphosphate and 50% zinc acetate;

[0106] Other conditions are the same as those in Example 1.

[0107] Comparative Example 5

[0108] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of sodium tripolyphosphate, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0109] Other conditions are the same as those in Example 1.

[0110] Comparative Example 6

[0111] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0112] In terms of mass percentage, the composite retarder is 50% disodium EDTA and 50% polyacrylic acid;

[0113] Other conditions are the same as those in Example 1.

[0114] Comparative Example 7

[0115] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of disodium EDTA, 18 parts of admixture, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0116] Other conditions are the same as those in Example 1.

[0117] Comparative Example 8

[0118] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 10 parts of fly ash microspheres, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0119] Other conditions are the same as those in Example 1.

[0120] Comparative Example 9

[0121] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of silica fume, 10 parts of fly ash microbeads, 2 parts of carbon nanotubes, 2 parts of carbon fibers and 16 parts of water;

[0122] Other conditions are the same as those in Example 1.

[0123] Comparative Example 10

[0124] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microspheres, 2 parts of carbon fiber and 16 parts of water;

[0125] Other conditions are the same as those in Example 1.

[0126] Comparative Example 11

[0127] A magnesium phosphate cement, the raw materials of which are, by weight: 70 parts of dead-burned magnesium oxide powder, 32 parts of phosphate, 15 parts of composite retarder, 18 parts of admixture, 10 parts of fly ash microspheres, 2 parts of carbon nanotubes and 16 parts of water;

[0128] Other conditions are the same as those in Example 1.

[0129] The setting time of the magnesium phosphate cement provided in Examples 1 to 10 and Comparative Examples 1 to 11 was determined according to the test method of "setting time" in GB / T1346-2011 "Test Method for Standard Consistency, Setting Time and Stability of Cement"; the compressive strength of the magnesium phosphate cement provided in Examples 1 to 10 and Comparative Examples 1 to 11 was tested at 1 day, 3 days and 28 days according to "Determination of Compressive Strength" in T / CMMA10-2023 "Magnesium Phosphate Composite Materials", and the results are shown in Table 1:

[0130] Table 1 Setting time and compressive strength of magnesium phosphate cement provided by Examples 1 to 10 and Comparative Examples 1 to 11

[0131]

[0132]

[0133] Table 1 is analyzed: It can be seen from the changes in the setting time in Examples 1 to 5 and Comparative Examples 1 to 3 that with the increase in the amount of the composite retarder in the high-strength retarded magnesium phosphate cement, the setting time of the high-strength retarded magnesium phosphate cement shows a significant trend of improvement. When the amount of the composite retarder changes within 3 to 15 parts, the setting time of the high-strength retarded magnesium phosphate cement changes within a period of tens of minutes to several hours, indicating that the composite retarder provided by the present invention can have a good retarding effect, and the setting time of the high-strength retarded magnesium phosphate cement can be controlled by controlling the amount of the composite retarder, so that the high-strength retarded magnesium phosphate cement is suitable for different application scenarios; it can be seen from the comparison of Examples 5 to 10 that when the amount of the composite retarder is the same, with the increase in the amount of the admixture, the setting time of the magnesium phosphate cement also shows a trend of a small increase, indicating that the admixture can also have a certain retarding effect and can also improve the mechanical properties of the magnesium phosphate cement; it can be seen from Examples 1 and 11 that without adding aggregate The prepared magnesium phosphate cement has a very high compressive strength, and after adding aggregate, its compressive strength can be further improved, thereby obtaining an ultra-high performance magnesium phosphate cement composite material; by comparing Example 1 with Comparative Examples 4 to 7, it can be seen that when the amount of retarder is the same, the composite retarder formed by using a single type of retarder or two retarders has a significantly worse retarding effect than the composite retarder provided by the present invention, indicating that the composite retarder provided by the present invention has a better retarding effect; by comparing Example 1 with Comparative Example 8, it can be seen that when the addition of admixtures is omitted, the setting time and mechanical properties of magnesium phosphate cement are significantly reduced, indicating that admixtures can improve the retarding effect and the mechanical properties of magnesium phosphate cement; by comparing Example 1 with Comparative Examples 9 to 10, it can be seen that when carbon fibers or carbon nanotubes are omitted, the setting time of magnesium phosphate cement does not change significantly, while the mechanical properties of magnesium phosphate cement are significantly reduced, indicating that carbon fibers and carbon nanotubes can improve the mechanical properties of magnesium phosphate cement.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength slow-setting magnesium phosphate cement, comprising the following raw materials, by weight: 60-95 parts of dead-burned magnesium oxide powder, 20-50 parts of phosphate, 3-15 parts of composite retarder, 5-20 parts of admixture, 8-14 parts of fly ash microspheres, 1-2 parts of carbon nanotubes, 1-5 parts of carbon fibers and 5-30 parts of water; The composite retarder comprises sodium tripolyphosphate, zinc acetate, disodium EDTA and polyacrylic acid; and the admixture comprises phosphorus slag powder and silica fume.

2. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: The average particle size of the dead-burned magnesium oxide powder is 30-40 μm, and the content of magnesium oxide in the dead-burned magnesium oxide powder is ≥92%.

3. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: The phosphate includes one or two of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, aniline hypophosphite and isopropanolamine phosphate.

4. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: Calculated by mass percentage, the composite retarder comprises 27-43% of sodium tripolyphosphate, 12-25% of zinc acetate, 17-22% of disodium EDTA and the balance of polyacrylic acid.

5. The high-strength slow-setting magnesium phosphate cement according to claim 1 or 4, characterized in that: Calculated by mass percentage, the composite retarder comprises 30-35% of sodium tripolyphosphate, 15-20% of zinc acetate, 18-21% of disodium EDTA and the balance of polyacrylic acid.

6. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: The mass ratio of the phosphorus slag powder to the silica fume is 1:(0.1-2).

7. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: The average particle size of the fly ash microbeads is ≤0.5 μm, and the specific surface area of ​​the fly ash microbeads is ≥1000 m 2 / kg.

8. The high-strength slow-setting magnesium phosphate cement according to claim 1, characterized in that: The parameters of the carbon fiber include: a length of 2 to 10 mm, a diameter of 10 to 50 μm, a tensile strength of 1500 to 2400 MPa, and a breaking elongation of 8 to 12%.

9. The method for preparing the high-strength slow-setting magnesium phosphate cement according to any one of claims 1 to 8, comprising the following steps: (1) mixing dead-burned magnesium oxide powder, phosphate, admixture, fly ash microbeads, carbon nanotubes and carbon fibers to obtain a mixture; (2) mixing the composite retarder and water, and then adding the mixture obtained in step (1) to stir, and finally curing to obtain high-strength retarded magnesium phosphate cement.

10. Use of the high-strength slow-setting magnesium phosphate cement according to any one of claims 1 to 8 or the high-strength slow-setting magnesium phosphate cement prepared by the preparation method according to claim 9 in rapid repair and solidification of harmful and radioactive materials.

Citation Information

Patent Citations

  • Delayed coagulation method of kalium-based magnesium phosphate cement

    CN102659450A

  • Phosphorus oxide magnesium gel material for 3D printing house

    CN106396603A

  • Delayed-coagulation high-toughness magnesium phosphate cement road rapid repair material

    CN111056815A

  • Magnesium phosphate cement with strong setting time adjustability

    CN113493321A

  • Retarder suitable for ammonium magnesium phosphate cement system and use method thereof

    CN113772986A

Cited By

  • Environment-friendly green cement as well as preparation method and application thereof

    CN121735599A

  • An environmentally friendly green cement-based material, its preparation method and application

    CN121735599B